The Glass Cliff – Women's Thrive to Save Poor Performance and how to Approach it in the Workplace - Julia Vetter (Junior Management Science (JUMS), 2021)
For decades the rise of women to leadership positions in the workplace has been a conspicuous matter on a global spectrum. Women are challenging the prospects that were once emplaced upon them and continue to break the forefronts of opportunity that face them. This thesis brings life to Eleanor Roosevelt's quote "A woman is like a tea bag: you never know how strong she is until she gets into hot water" by exploring the glass cliff phenomenon. Stating that women have a higher chance of rising into leadership positions during a time of poor company performance, the research conducted for this paper aims to look further into the background of the principles creating this subtle form of discrimination. To discover the root cause of the glass cliff phenomenon, this thesis aims to understand when, how and why these positions are conceived furthering on how to approach the changes coveted by modern society regarding female leadership. This composition takes into account an amalgamation of existing research and the individual empirical research conducted, explaining the causation behind the glass cliff through understanding the biases, stereotypes and societal dynamics that enable glass cliff positions in the workplace.
Keywords: 650; Glass cliff; women in leadership; discrimination; equality; management